Distinct microbiome dysbiosis and epigenetic anomaly in esophageal adenocarcinoma and its underlying Barrett’s esophagus - Takuya Shijimaya; Tomomitsu Tahara; Jumpei Yamazaki; Sanshiro Kobayashi; Yasushi Matsumoto; Naohiro Nakamura; Yu Takahashi; Takashi Tomiyama; Toshiro Fukui; Tomoyuki Shibata; Makoto Naganuma (Clinical Epigenetics)
Abstract Interaction between host genotoxic changes and mucosa-associated microbiome (MAM) dysbiosis may have a role in various digestive cancers. We investigated MAM in Barrett’s esophagus (BE) and esophageal adenocarcinoma (EAC) progression sequence and its association with host genotoxic changes. 16S rRNA gene sequencing was performed in three different groups of biopsies from nonneoplastic BE from patients without cancer (N, normal group; n = 47) and with EAC (ADJ, adjacent group; n = 27). Endoscopic biopsies were also obtained from EAC tissues (T, tumor group; n = 22). Results were correlated with TP53 mutation, telomere length and DNA methylation of candidate genes (N33, DPYS, SLC16A12, miR124A3 and miR34bc). Genome-wide DNA methylation examined by reduced representation bisulfite sequencing (RRBS) was available for 32 samples (n = 12 for N, n = 12 for ADJ and n = 22 for T groups). Lower microbial alpha diversity measures were observed in ADJ/T groups relative to N group and associated with higher mean Z score DNA methylation of candidate genes. Specific genera (n = 16) with significant change between ADJ/T groups relative to N group occurred mostly in ADJ group (13/16) and half of them (8/16) were associated with DNA methylation status. Integrated MAM and genome-wide methylation analysis demonstrated that hyper-methylated sites, associated with lower alpha diversity measures dominantly occurred within near the transcription start site, codifying genes were involved in metabolic processes. Our result shows that microbial dysbiosis in EAC mostly occurs in adjacent BE and such dysbiosis was associated with DNA methylation status, offering support for a pathogenic role of interaction between host genotoxic changes and MAM in this tumor type.